Dual colorimetric and fluorogenic probes for visualizing tyrosine phosphatase activity. Issue 14 (1st February 2017) - Biswas, Suvendu; McCullough, Brandon S.; Ma, Elena S.; LaJoie, Dollie; Russell, Colin W.; Garrett Brown, D.; Round, June L.; Ullman, Katharine S.; Mulvey, Matthew A.; Barrios, Amy M.
Abstract : Two resorufin-based substrates were developed, providing sensitive fluorogenic readouts for PTP activity in vitro and in living cells. Abstract : Two resorufin-based substrates for protein tyrosine phosphatase (PTP) activity have been synthesized. These substrates provide sensitive fluorogenic readouts of PTP activity in vitro and in living cells at both acidic and neutral pH. In addition, the presence of the pathogenic bacteria Staphylococcus aureus was detected visually using a colorimetric readout.